Pretreatment Inflammation-Based Markers Predict Survival Outcomes in Patients with Early Stage Hepatocellular Carcinoma After Radiofrequency Ablation. Issue 1 (December 2018) - Chu, Michelle; Shen, Chien-Heng; Chang, Te-Sheng; Xu, Huang-Wei; Yen, Chih-Wei; Lu, Sheng-Nan; Hung, Chao-Hung
Abstract The prognostic significance of various systemic inflammation‐based markers has been explored in different cancers after surgery. This study aimed to investigate whether these markers could predict outcomes in patients with early-stage hepatocellular carcinoma (HCC) undergoing radiofrequency ablation (RFA). One hundred eighteen patients with newly diagnosed HCC within the Milan criteria receiving RFA as initial therapy were retrospectively enrolled. Pretreatment inflammation-based markers including the neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR) and prognostic nutritional index (PNI), together with other clinicopathologic parameters were collected. Cumulative overall survival (OS) and recurrence-free survival (RFS) were estimated by the Kaplan-Meier method and by multivariate analysis using Cox proportional hazard model. The 1-, 3-, and 5-year OS rates of patients were 90%, 67%, and 52%, respectively. Kaplan-Meier curves showed that baseline high NLR ≥ 2.5 (p = 0.006), low PNI < 40 (p = 0.005), history of end-stage renal disease (ESRD) (p = 0.005), non-Child-Pugh class A (p = 0.001) and elevated alpha-fetoprotein (AFP) ≥ 200 ng/mL (p = 0.005) significantly associated with the poor OS, whereas high PLR ≥ 100 did not. By multivariate analysis, high NLR ≥ 2.5 (hazard ratio (HR) 1.94; 95% confidence interval (CI), 1.05–3.59;p = 0.034), low PNI < 40 (HR 0.38; 95% CI, 0.20–0.72;p = 0.003), ESRD history (HR 3.60; 95% CI, 1.48–8.76;p = 0.005) and elevated AFP ≥ 200 ng/mL (HR 4.61; 95% CI, 1.75–12.13;p = 0.002) were independent factors. An elevated AFP level of ≥200 ng/mL was the significant factor associated with intrahepatic new RFS by univariate and multivariate analyses. In conclusion, pretreatment NLR and PNI are simple and useful predictors for OS in patients with early-stage HCC after RFA.